A comparative study of 3 treatment modalities for mandibular angle fractures - Dulabh, Shailen (My University, 2017)
Introduction: The mandibular angle fracture remains one of the most common mandibular fractures with a reported incidence of ~20 – 40%. Its treatment is rife with controversy with a reported global complication rate of ~30%. Aim: The purpose of the study is to determine the optimum management of the compound, isolated mandibular angle fracture. Methods and materials: A prospective, randomised, study was carried out within the department where all cases of isolated, compound, mandibular angle fractures were allocated to 1 of the three treatment groups: Group1: Superior border wire; Group2: Single miniplate; Group3: Double miniplate. The patients were assessed for the presence of post-operative infection, malocclusion and fixation failure and the outcomes were correlated. The data was analysed statistically and reported upon using STATA. Results: 75 patients were included in the study with 25 patients per group. Complication rates were equal between the miniplate groups (16%), with the Superior border wire having the best outcomes. The average ―days to surgical fracture repair post-injury‖ (p = 0.08) and the category of ―severely displaced fractures‖ (>5mm) are the factors shown to increase the incidence of complications, p = 0.02. Overall a 13.3% complication rate was noted. Conclusion: The use of 2 miniplates seems to offer no benefit over a single miniplate. In stark contrast to previous global findings, fixation using a superior border wire with intermaxillary fixation (IMF) showed the best outcomes with a 92% success rate and its usage should be reaffirmed as a cost-effective alternative in a resource-constrained environment.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Dentistry, Maxillo, Facial and Oral Surgery Johannesburg, 2017
Keywords: Mandibular Fractures